Morphological Characteristics, Microscopical Characteristics, and Qualitative Phytochemical Screening of Commelina diffusa Burm.f. - Loi, Vu Duc; Thi Anh, Pham; Hong Duong, Le; Xuan Tung, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Acticle in Press, 2026)
Commelina diffusa Burm.f. (Commelinaceae) is a perennial creeping herb distributed widely in tropical and subtropical regions, including Vietnam. Traditionally, this plant has the effect of clearing heat, detoxifying, diuretic, treating cough, high blood pressure and gonorrhea. In this study, we aims to describe the morphological and microscopical characteristics of C. diffusa and qualitatively screened its phytochemical groups. The results showed that the research sample had all the characteristics of C. diffusa such as: creeping stem, alternately arranged simple leaves, red striped leaf sheaths, blue flowers, 3-celled capsules containing black seeds with reticulated veins. Microscopical analysis of stems, leaves, and powdered materials showed typical anatomical features of the genus Commelina . Qualitative phytochemical screening revealed the presence of alkaloids, flavonoids, coumarins, tannins, organic acids, carotenes, and fatty acids. These findings provide scientific evidence for species authentication and contribute to the potential medicinal use of C. diffusa in Vietnam.